Large for Gestational Age Babies Born To Diabetic and Non-Diabetic Mothers - Halim, AKM Yunus; Huda, Syed Nazmul; Ahmed, Luthfor; Begum, Shireen; Banu, Laila Arjumand (Journal of Armed Forces Medical College, Bangladesh, 2017)
Introduction: Foetal growth and development is a complex process that involves the interrelationship among the mother, placenta and fetus. Both high and low birth weight infants are associated with the highest prevalence of diabetes. Women with diabetes are at greater risks, because of their pregnancy related complications. Objective: To compare the characteristics of groups of LGA (large for gestational age) babies born to prediabetic mothers (DM) and gestational diabetic mothers (GDM) with control infants born to apparently healthy non-diabetic mothers (NDM). Materials and Methods: This was a prospective cohort study of 251 newborn-mother pairs (n: DM=86; GDM=86 and NDM=79) recruited from the Bangladesh Institute of Research and Rehabilitation in Diabetes, Endocrine and Metabolic Disorders (BIRDEM), Dhaka. Detailed anthropometric measurements of infants were taken at birth in the hospital. LGA babies had birth weights greater than the 90th percentile for their gestational age for sex and SGA (small for gestational age) babies usually had birth weights below the 10th percentile for babies of the same gestational age for sex. Results: Only 10(11.6%) babies were found LGA in the GDM group as opposed to 3 each for DM and NDM group. There was a significant group difference in the incidences of SGA babies. Around 16% to 18% were there in the DM and GDM groups, as opposed to much higher rate (30.4%) in the NDM group. Conclusion: Newborns from both DM and GDM groups showed greater values compared to that of the NDM group in all anthropometric measures except length and head circumference suggesting intrauterine growth acceleration in them. Journal of Armed Forces Medical College Bangladesh Vol.13(1) 2017: 117-123